2004
DOI: 10.1197/j.aem.2003.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of a Structured Interview Scoring Instrument for a Canadian Postgraduate Emergency Medicine Training Program

Abstract: The reliability of the overall interview scores was very high. The intraclass correlations for each interviewer's VAS scores were also high, but interrater correlations within interview teams were moderate and not higher than those across interview teams. This study suggests that an interview assessment instrument can be highly reliable overall and that interviewers base scores on an overall global impression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…The interview, however, is a less valid and less reliable method that mostly assesses knowledge 7 . As a result, modifications to the interview, such as the structured standardised interview, 8 and the multiple mini‐interview (MMI), 3 have been tried with considerable success. However, unless modified to assess live interpersonal interactions and practical skills, as in some MMI stations, the classical interview format cannot assess practical skills.…”
Section: Step 5: Identifying Selection Methodsmentioning
confidence: 99%
“…The interview, however, is a less valid and less reliable method that mostly assesses knowledge 7 . As a result, modifications to the interview, such as the structured standardised interview, 8 and the multiple mini‐interview (MMI), 3 have been tried with considerable success. However, unless modified to assess live interpersonal interactions and practical skills, as in some MMI stations, the classical interview format cannot assess practical skills.…”
Section: Step 5: Identifying Selection Methodsmentioning
confidence: 99%
“… 51 MMI may mitigate bias by reducing the variability of questions and limiting the impact of both the interview context and interviewer biases (e.g., gender, race, or leniency/stringency tendency). 51 , 54 , 55 , 56 MMIs include scenarios that may provide insight into an applicant's non-cognitive domains, such as interpersonal and communication skills. 51 Studies have shown improved reliability as well as perceived fairness, effectiveness, and acceptability, 55 , 56 , 57 , 58 although some applicants felt it difficult to establish a connection with interviewers during MMIs.…”
Section: Interview Content and Evaluationmentioning
confidence: 99%
“…We incorporated strong assessment practices such as criterion-referenced rating scales 22 and multiple assessments from diverse raters. 23 Furthermore, we assessed characteristics that are associated with success in residency (reference letters and publication numbers 17 ) and have demonstrated reliability (MMIs 24 consisting of structured interviews with predefined assessment tools 25 ). Informal communications with other programs suggest that our use of simultaneous cloud-based rating, Z-scores, and heat maps are innovations that are not commonly used.…”
Section: Comparison With Previous Workmentioning
confidence: 99%